Endoparasite survey in Amazonian manatees (Trichechus inunguis) under rehabilitation in the Peruvian Amazon - Philipp Sziderics; Alessandra R. Medrano Zavala; Edmundo Guadalupe Parada Lopez; E. Leonardo Davila Panduro; Juan J.E. Sanchez Babilonia; Maria S. Unterköfler; David Ebmer; Emmanouil A. Koumantakis; Jim W. Ruiz Pezo; Franco I. Macedo Tafur; Luis A. Gomez-Puerta; Hans-Peter Fuehrer (International Journal for Parasitology: Parasites and Wildlife)
Manatee populations are declining worldwide, and all currently existing species are considered vulnerable by the IUCN. The most common problems during nurturing young Amazonian manatees, Trichechus inunguis, in rescue centres are of gastrointestinal nature leading to inappetence, diarrhoea, cachexia and even death. Endoparasites play an important role in the well-being of wildlife in captivity as well as in the wild, though information about relevant protozoan and metazoan endoparasites in Amazonian manatees is still scarce. Therefore, this study aimed to find endoparasites in T. inunguis by analyzing faecal samples from 23 Amazonian manatees which were kept in rescue centres in the Peruvian Amazon. The samples were screened for protozoan and metazoan parasites using coproscopical analysis and molecular tools. Out of twenty juvenile animals eleven were positive for at least one Eimeriidae. Two morphologically different, not yet genetically described Eimeria species were identified. One of them seems to be Eimeria trichechi which has only been described once in 1984 in Amazonian manatees from Brazil. It was not found to lead to clinical symptoms of coccidiosis in this study. The second, Eimeria sp. Type B was associated with clinical coccidiosis in a young Amazonian manatee, which showed gastrointestinal symptoms including diarrhoea, inappetence and cachexia. No other protozoan or metazoan parasite were detected in any of the samples. The present study is the first to investigate endoparasites in Amazonian manatees using molecular tools and is the first to identify an Eimeria species that could be associated with clinical symptoms in T. inunguis. With information from our study rescue centres can improve monitoring of parasites more effectively to reduce morbidity and mortality rates among rehabilitated manatees as well as improve the health status and fitness of animals for a successful release back into the wild.